INFLUENCE OF CORPORATE SOCIAL APPLICATION RESPONSIBILITY TO PROFITABILITY IN ALMEERA ATELIER - Khintari, Muhammad Amien; Fauziyah, Azizah; Koeswandi, Tika Annisa Lestari (A Social Science and Entrepreneurship Journal, 2022)
The purpose of this study, namely to find out the general description of Corporate Social Responsibility (CSR) and profitability at Almeera Atelier and determine the effect of Corporate Social Responsibility on profitability at Almeera Atelier. The object of this research is Almeera Atelier. The method used in this study is a quantitative research method with descriptive and associative approaches because of the variables that will be examined in relation to it and its purpose is to present a structured picture. The results of this study have an influence in the implementation of CSR on increasing profitability.